Lipoprotein lipase-catalyzed hydrolysis of phosphatidylcholine of guinea pig very low density lipoproteins and discoidal complexes of phospholipid and apolipoprotein: effect of apolipoprotein C-II on the catalytic mechanism - K Shirai; T J Fitzharris; M Shinomiya; H G Muntz; J A Harmony; R L Jackson; D M Quinn (Journal of Lipid Research, 1983)
To elucidate the mechanism by which apolipoprotein C-II (apoC-II) enhances the activity of lipoprotein lipase (LpL), discoidal phospholipid complexes were prepared with apoC-III and di[(14)C]palmitoyl phosphatidylcholine (DPPC) and containing various amounts of apoC-II. The rate of DPPC hydrolysis catalyzed by purified bovine milk LpL was determined on the isolated complexes. The rate of hydrolysis was optimal at pH 8.0. Analysis of enzyme kinetic data over a range of phospholipid concentrations revealed that the major effect of apoC-II was to increase the maximal velocity (V(max)) some 50-fold with a limited effect on the Michaelis constant (K(m)). V(max) of the apoC-III complex containing no apoC-II was 9.2 nmol/min per mg LpL vs. 482 nmol/min per mg LpL for the complex containing only apoC-II. The effect of apoC-II on enzyme kinetic parameters for LpL-catalyzed hydrolysis of DPPC complexes was compared to that on the parameters for hydrolysis of DPPC and trioleoylglycerol incorporated into guinea pig very low density lipoproteins (VLDL(p)) which lack the equivalent of human apoC-II. Tri[(3)H]oleoylglycerol-labeled VLDL(p) were obtained by perfusion of guinea pig liver with [(3)H]oleic acid. Di[(14)C]palmitoyl phosphatidylcholine was incorporated into the VLDL(p) by incubation of VLDL(p) with sonicated vesicles of di[(14)C]palmitoyl phosphatidylcholine and purified bovine liver phosphatidylcholine exchange protein. The rates of LpL-catalyzed hydrolysis of trioleoylglycerol and DPPC were determined at pH 7.4 and 8.5 in the presence and absence of apoC-II. In the presence of apoC-II, the V(max) for DPPC hydrolysis in guinea pig VLDL(p) increased at both pH 7.4 and pH 8.5 (2.4- and 3.2-fold, respectively); the value of K(m) did not change at either pH (0.23 mm). On the other hand, the kinetic value of K(m) for triacylglycerol hydrolysis in the presence of apoC-II decreased at both pH 7.4 (3.05 vs. 0.54 mm) and pH 8.5 (2.73 vs. 0.62 mm). These kinetic studies suggest that apoC-II enhances phospholipid hydrolysis by LpL in apoC-III-DPPC discoidal complexes and VLDL(p) mainly by increasing the V(max) of the enzyme for the substrates, whereas the activator protein primarily causes a decrease in the apparent K(m) for triacylglycerol hydrolysis.-Shirai, K., T. J. Fitzharris, M. Shinomiya, H. G. Muntz, J. A. K. Harmony, R. L. Jackson and D. M. Quinn. Lipoprotein lipase-catalyzed hydrolysis of phosphatidylcholine of guinea pig very low density lipoproteins and discoidal complexes of phospholipid and apolipoprotein: effect of apolipoprotein C-II on the catalytic mechanism.